Twenty years of natalizumab in multiple sclerosis: lessons learned and future outlook - Klotz, Luisa; Berger, Thomas; Brownlee, Wallace J.; Chan, Andrew; Lycke, Jan; Oreja-Guevara, Celia; Palavra, Filipe; Sacca, Francesco; Sejbaek, Tobias; Weber, Martin S.; Giovannoni, Gavin (Therapeutic advances in neurological disorders, 2025)
Twenty years on from its initial approval as the first monoclonal antibody for the treatment of multiple sclerosis (MS), natalizumab remains a valuable high-efficacy treatment option for people with relapsing-remitting MS, with robust real-world evidence supporting its long-term efficacy and well-characterized safety profile, provided that the risk of progressive multifocal leukoencephalopathy (PML) is monitored and mitigated. This review explores the long-term clinical impact of natalizumab. It draws on two decades of experience to guide treatment strategies with natalizumab, including its use early in the disease course, switching to natalizumab, its use during vaccination, and PML risk management and exit strategies. Guidance on the use of natalizumab in pregnant and breastfeeding women with MS, children with MS, and people with comorbidities is discussed, along with reflections on what has been learned from 20 years with natalizumab, and what the future holds for this impactful treatment in MS and beyond.